Effect of Green Tea on the Level of Salivary Interleukin-1 Beta in Patients with Chronic Periodontitis: A Randomized Clinical Trial - Gita Rezvani; Ferial Taleghani; Maryam Valizadeh (Hindawi Limited, 2022)
Aim. Interleukin-1 beta (IL-1β) is one of the major biomarkers involved in the pathogenesis of chronic periodontitis. The aim of this study was to evaluate the changes in salivary IL-1β concentration in patients with chronic periodontitis following daily consumption of green tea. Methods and Materials. Thirty patients with an average age of 45.8 years suffering from chronic periodontitis were randomly assigned into 2 groups (i.e., experimental and control groups). Besides receiving phase 1 periodontal treatment (scaling and root planning (SRP)), the experimental group drank green tea for a period of 6 weeks. To measure the concentration of salivary IL-1β, saliva samples were taken from both groups at 2 time points, i.e., prior to SRP (time point 1 (T0)) and after 6 weeks (time point 2 (T1)). The nonparametric Wilcoxon test was used to examine and compare the changes in the concentration of salivary IL-1β in each group relevant to the 2 time points (T0 and T1). Data were submitted to statistical analysis. Results. At the end of the study period, a significant reduction (P=0.0001) in the concentration of salivary IL-1β was observed in the experimental group (A). As for the control group (B), however, there was no significant change (P=0.307) in the concentration of salivary IL-1β after 6 weeks following phase 1 periodontal treatment. Conclusion. Green tea supplementation, in addition to SRP, may reduce salivary IL-1β levels in patients with chronic periodontitis for a period of 6 weeks.